Does the Duration of Cervical Radicular Symptoms Impact Outcomes After Anterior Cervical Discectomy and Fusion?. Issue 9 (November 2019) - Basques, Bryce A.; Ahn, Junyoung; Markowitz, Jonathan; Harada, Garrett; Louie, Philip K.; Mormol, Jeremy; Varthi, Arya; Goldberg, Edward J.; An, Howard S.
Abstract : Study Design: Retrospective cohort study. Objective: To compare clinical outcomes after anterior cervical discectomy and fusion (ACDF) based on preoperative duration of radiculopathy symptoms. Summary of Background Data: There is no clear indication of when outcomes after ACDF become less effective in the setting of acute versus chronic symptoms from cervical nerve root compression. Materials and Methods: A retrospective cohort study of consecutive patients who underwent an ACDF between 2008 and 2015 for radiculopathy was performed. Patients were divided into 3 groups: radicular symptoms lasting for <6 months, symptoms lasting for 6–12 months, and those with symptoms for ≥12 months. Neck Disability Index (NDI) and Visual Analog Scale (VAS) scores for both the neck and arms were obtained at preoperative and final postoperative visits. Radiographs were assessed for adjacent segment degeneration, fusion, and subsidence. Bivariate and multivariate regressions were subsequently used to compare outcomes between groups. Results: A total of 379 patients were included. Patients with symptoms lasting for 6–12 months and those with symptoms lasting for ≥12 months had worse preoperative VAS neck pain compared with patients with symptoms lasting for < 6 months ( P =0.000 and P =0.004, respectively). Patients with symptoms lasting for ≥12 months had worse baseline functional status compared with patients with symptoms lasting for <6 months ( P =0.009). At final follow-up, there were no significant differences in VAS neck, VAS arm, or NDI between symptom duration groups. However, differences in outcomes were noted when considering the type of preoperative symptom. Patients with pain symptoms of ≥12 months had worse preoperative VAS neck ( P =0.001), VAS arm ( P =0.008), and NDI ( P <0.001) and had significantly worse final VAS arm ( P =0.019) and NDI ( P =0.016) compared with patients with preoperative pain symptoms lasting for <6 months. The overall reoperation rate was 4.5%. Fusion was achieved in 97.6% of the patients, and subsidence was observed in 5.5%. There were no significant differences in the risk of adjacent segment degeneration, reoperations, fusion rates, or subsidence rates based on preoperative symptom duration. Conclusions: Despite worse preoperative neck pain and functional status in patients with preoperative duration of symptoms >6 months, there were no differences in final clinical outcomes across groups.